UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MURID KELAS VI (ENAM) MUATAN IPAS MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DI SDN KELAYAN TIMUR 2 - Aulia Wati, Noor; Mukarramah; Mayanti Sari, Putri; Amberansyah; Saudah, Masnun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low levels of student activity and learning outcomes in the Natural and Social Sciences (IPAS) subject among Grade VI students at SDN Kelayan Timur 2. The underlying cause was a teaching approach that remained monotonous and one-way. The objective of this study was to improve student activity and learning outcomes. This research was conducted as Classroom Action Research (CAR) in a collaborative manner across two cycles. The subjects of the study were 24 Grade VI students at SDN Kelayan Timur 2. Data collection techniques included observation, learning outcome tests, and documentation. Data analysis was performed using a descriptive-comparative approach by comparing results from the pre-cycle, Cycle I, and Cycle II. The results indicated a significant improvement. During the pre-cycle, student activity was only 38%, and the learning mastery rate was 38%. Following the Cycle I intervention, student activity rose to 58%, and learning mastery reached 63%. In Cycle II, student activity reached 88%, and learning mastery reached 92%. Thus, it can be concluded that the implementation of the Problem-Based Learning (PBL) model proved effective in enhancing the activity and learning outcomes of Grade VI students in the IPAS subject at SDN Kelayan Timur 2.